Hibridismo e cultura pop: alienígenas como ícones religiosos em contextos ayahuasqueiros e não ayahuasqueiros = Hybridism and pop culture: aliens as religious icons in Ayahuasca and non-Ayahuasca contexts - Santos, Ricardo Assarice dos (Rever, 2020)
Aliens have become a prolific pop icon, especially throughout the 20th century. Western culture has seen the proliferation of first-hand accounts of contacts with beings from other planets, while the imagination has echoed and nurtured such an icon. As one result, alleged aliens have reinforced and expanded their religious dimension, especially among people for whom traditional religions no longer have sufficient appeal. A central process for the consolidation of aliens as pop icons and holders of religious functions and roles among diverse people is cultural hybridization, which is discussed in this article – based on Peter Burke’s theory (2001) – by comparing contexts that make use of the ceremonial drink Ayahuasca and that do not.